Suitability of crushed sandcrete block (CSB) as a partial replacement for fine aggregate in concrete - Joshua Adoyi Akor; Leonard Agbo Onjefu; Joseph Ejelikwu Edeh; Ademilade Joseph Olubambi (Journal of Building Materials and Structures)
The suitability of crushed Sandcrete block (CSB) for use as a partial replacement for fine aggregate in concrete was examined. The physical and mechanical properties of the crushed Sandcrete block and river sand were determined and compared. The specific gravity of the crushed Sandcrete block was found to be 2.58 while that for river sand was 2.66. The concrete with compressive strength of 25N/mm2 at 28 days’ hydration period was calculated for the normal mixture as the control. The percentage mix of the fine aggregate was substituted with CSB in different mix proportions of 0:1(0%), 1:3(25%), 1:2(33.3%), 1:1(50%), 2:1(66.7%), 3:1(75%) and 1:0(100%) of crushed Sandcrete block and river sand by weight as fine aggregate. The concrete cubes were cured, and compressive strength tests were carried out at 7, 14, and 28 days. It was observed that the 28-day density and compressive strength for concrete cubes with crushed Sandcrete block alone as fine aggregate (i.e. 100%) were found to be 2420kg/m³ and 22N/mm² respectively compared to the 0:1(0%) proportion which was found to be 2485kg/m³ and 26N/mm² respectively. It was observed that the density and compressive strength reduced with the increasing addition of CSB in all the proportions.